Use of Stakeholder Feedback to Develop an App for Vestibular Rehabilitation–Input From Clinicians and Healthy Older Adults - DSilva, Linda J.; Skop, Karen M.; Pickle, Nathan T.; Marschner, Katherine; Zehnbauer, Timothy P.; Rossi, Michael; Roos, Paulien E. (Frontiers in Neurology, 2022)
Close to half people over 60 years of age experience vestibular dysfunction. Although vestibular rehabilitation has been proven effective in reducing dizziness and falls in older adults, adherence to exercise programs is a major issue and reported to be below 50%. Therefore, this research aimed to develop an app with gaming elements to improve adherence to exercises that are part of vestibular rehabilitation, and to provide feedback to increase the accuracy during exercise performance. A clinician-informed design was used where five physical therapists were asked identical questions about the exercises they would like to see in the app, including their duration and frequency. Games were developed to train the vestibulo-ocular (VOR) reflex using VOR and gaze shifting exercises; and to train the vestibulo-spinal system using weight shifting and balance exercises. The games were designed to progress from simple to more complex visuals. The games were controlled by an Inertial Measurement Unit placed on the head or anterior waist. The app was tested on ten healthy females (69.1±5.1 years) with no prior history of vestibular dysfunction or complaints of dizziness. Participants completed gaze stabilization and balance exercises using the app and provided feedback on the user interface, ease of use, usefulness and enjoyment using standardized questionnaires and changes they would like to see in the form of open-ended questions. In general, participants reported that they found the app easy to use, the user interface was friendly, and they enjoyed playing the games due to the graphics and colors. They reported that the feedback provided during the exercise session helped recognizing their mistakes and motivated to do better. However, some elements of the app were frustrating due to incomplete instructions and inability to distinguish game objects due to insufficient contrast. Feedback received will be implemented in a revised version which will be trialed in older adults with dizziness due to vestibular hypofunction. We have demonstrated that the “Vestibular AppTM” created for rehabilitation with gaming elements was found to be enjoyable, useful, and easy to use by healthy older adults. In the long term, the app may increase adherence to vestibular rehabilitation.